A critical examination of industrial conflict in labour- management relations - Johnson Iyiola Ogundele; Samuel Ayodele Majekodunmi (Business & Management Compass)
The paper examines the occurrence of industrial conflict between labour unions and management in the workplace. The inevitability of conflict stems from the economic interest both parties want to satisfy at any point in time in their work relations which are at variance. The economic interest of both parties is inversely related and this will always reinforce disharmony of interest in the workplace. The theoretical analysis focused on conflict theory by Karl Marx and theory of industrial pluralism by Sidney and Beatrice Webb. Essentially, causes of industrial conflict was brought to the fore, its consequences and resolution mechanism were expatiated.  Views of various schools of thought on conflict were examined together with functional and dysfunctional aspects of industrial conflict. Suggested measures to manage effectively the emergence of workplace conflict were also discussed. The study concluded that industrial conflict has become a recurring decimal in labour–management relations, however, the suggested measures to reduce and manage the preponderance of conflict should be followed in order to enhance workplace peace and harmonious labour management relations.